Effects оf аn Unsupervised Home Exercise Program to Improve Volunteer Firefighter Fitness аnd Occupational Performance: A Pilot Study - Bajić, Senka; Orr, Robin; Veljović, Dragoljub; Kukić, Filip (NBP. Nauka, bezbednosti, policija, 2025)
Volunteer firefighters perform the same job tasks as professional firefighter but may have lower levels of fitness and be at greater risk of cardiovascular disease. The aim of this study was to determine the effects of an 8-week unsupervised home exercise program on the physical fitness and occupational performance of volunteer firefighters. Firefighters (n=15 male) volunteered to participate. Outcome measures included measures of stature, health (blood pressure and percentage body fat (%BF)), fitness (cardiovascular endurance, muscular strength, power and endurance, flexibility) movement skills (i.e., Functional Movement Screen (FMS)) and occupational performance (stair climb, hose drag, equipment carry and victim drag). Between data collection points, participants undertook an unsupervised 8-week home exercise training program of 3 sessions per week plus corrective exercises based on FMS scores. Of the five firefighters that completed the program compliance rates were 47% (33-70%). Right hand grip strength and FMS scores im-proved significantly (p<0.05) with a trend towards improved blood pressure (p=0.054), and %BF (p=0.084). Given difficulties in providing a supervised exercise program for volunteer firefighters, an unsupervised home exercise program did lead to some improvements in their health and fit-ness. An unsupervised home exercise program may improve elements of firefighter fitness but participation rates and compliance are major challenges. Provision of an unsupervised home exercise program alone will potentially be of limited value. Future research should investigate means of improving unsupervised exercise program compliance in this population.